Active and passive beam application design guide. (ASHRAE, American Society of Heating, Refrigerating and Air-Conditioning Engineers, Inc., 2015)
"This book provides tools and guidance to design, commission, and operate active and passive beam systems to achieve a determined indoor climate. It also presents examples of active and passive beam calculations and selections"-- Provided by publisher
Revision of Chilled beam Application Guidebook, published by REHVA, 2004.
This version has I-P units listed first.
Keywords: Chilled beams (Air conditioning); elektronické knihy; electronic books